The Nature and Impact of Gendered Patterns of Peer Sexual Communications among Heterosexual Emerging Adults - Trinh, Sarah L. (J Sex Res, 2015)
Although previous research demonstrates that peers serve as top sexual informants and advisers, little is known about how peer sexual communications may be a gendered phenomenon. Do communications about sex and romantic relationships vary according to who is speaking to whom? The current study examined 517 college students' reports of male and female peers' communications of four sexual scripts and the associations between reports of such communications and participants' sexual attitudes and levels of sexual and dating experience. Results suggest that peer messages about sex and relationships vary by the gender of the recipient and the gender of the communicator. Women reported more frequent communications of all sexual scripts from female peers than did men. In terms of male peers' sexual communications, only one gender difference emerged: men reported receiving significantly fewer messages about the relational script than women. Compared to same-sex peer communications, there were more associations between other-sex peer communications and undergraduates' sexual attitudes and levels of sexual and dating experience. Implications for the role of same- and other-sex peers in sexual socialization are discussed.